Effectiveness of Mifepristone plus Misoprostol and Misoprostol alone in Cervical Ripening and Induction of Labour in Postdated Pregnancy - Ghimire, Asmita; Gurung, Geeta; Ojha, Bhuwan Prasad; Baral, Josie (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To compare the effectiveness of mifepristone plus misoprostol in pre-induction cervical ripening and induction of labour in uncomplicated post-dated primigravidae. Methods: It is a hospital based prospective comparative study enrolling 50 uncomplicated post-dated pregnancies in each group to determine the efficacy and safety of mifepristone and misoprostol with misoprostol alone for induction. It was conducted in Institute of Medicine. Computer software SPSS 20 was used for processing and analysis of the data. Chi-square test and paired sample t-test was used. Results: Comparing change in Bishops score among the two groups, no any statistically significant difference was seen. Sixty-six percent delivered vaginally in mifepristone group as compared to 42% in misoprostol group (p≤0.01). Rest delivered by caesarean section. No significant maternal side effects and complications were seen. Twenty-six percent in mifepristone group and 50% babies in misoprostol group developed fetal side effects (p=0.01). Conclusions: Mifepristone and misoprostol both bring favourable change in the Bishop’s score. Regarding success rate and fetal complications mifepristone seems to be effective and safe. Keywords: induction of labour, mifepristone, misoprostol, post-dated pregnancy